Diagnosis of Hepatocellular Carcinoma through Telehealth: A Unique Case Report - MUBASHEER ALI; AYESHA NAZNEEN; PRASHANT JANJAL (Journal of Clinical and Diagnostic Research, 2023)
Hepatocellular Carcinoma (HCC) is common among individuals with cirrhosis, regardless of the cause, but rare in those without cirrhosis. While HCC typically spreads to lymph nodes in the abdomen, lungs, and bones, metastasis to the cardiac region is relatively uncommon. Early screening and diagnosis are crucial for determining the feasibility and prognosis of HCC treatment. In addition to well-known causes such as alcohol consumption and viral hepatitis B and C, Non alcoholic Fatty Liver Disease (NAFLD) is emerging as a significant risk factor for cirrhosis, steatosis, and advanced liver fibrosis, contributing to the rise in HCC cases due to the increasing prevalence of metabolic syndrome. The present case report highlights a 71-year-old patient with HCC who was able to receive a timely diagnosis through telemedicine and initiate treatment with an oncologist. The patient underwent Intensity Modified Stereotactic Radiotherapy (IMSR) followed by bridge therapy with chemotherapy drugs. The treatment plan was implemented in July 2022, and the patient tolerated it well, remaining haemodynamically stable with no complaints.